Sumbawa cattle: a study of growth hormone (GH) gene variants and their association with biometric traits - P. W. Prihandini; H. Hasinah; A. P. Z. N. L. Sari; Y. A. Tribudi; L. Praharani; S. A. Asmarasari; E. Handiwirawan; B. Tiesnamurti; D. K. Robba; E. Romjali; A. Ibrahim (Brazilian Journal of Biology, 2024)
Abstract The growth hormone (GH) gene plays a vital role in regulating animal metabolism and body size, making it a potential candidate for influencing livestock performance. This study aimed to investigate the polymorphisms within the GH gene and their associations with 10 biometric traits in the Sumbawa cattle population of Indonesia. Biometric trait data and blood samples were collected from 112 Sumbawa cattle individuals, and their GH gene sequences were analyzed using two sets of primers for amplification. Seven single nucleotide polymorphisms (SNPs) were identified in the GH gene: g.442C>T, g.446G>C, g.558C>T, g.649C>A, g.1492C>A, g.1510C>A, and g.1578G>A. All SNPs were located in the intronic region except for SNP g.558C>T, which was found in the coding sequence (CDS) region. The SNP g.558C>T is classified as a synonymous variant. Haplotype analysis revealed a strong linkage disequilibrium between SNPs g.558C>T and g.649C>A. Distributions of genotypes and alleles of all SNPs were in agreement with the Hardy-Weinberg equilibrium (p > 0.05, χ2 < 15.56), except for SNPs g.446G>C and g.1492C>A. The association study showed that the SNP g.442C>T significantly (p < 0.05) affected HL, BL, SH, and PH traits in Sumbawa cattle. Additionally, the g.446G>C and g.558C>T were also found to be associated with PH and CC traits, respectively. The polymorphisms detected in the GH gene could have implications for selection programs to enhance desired biometric traits in Sumbawa cattle. Improving livestock productivity can be done by understanding genetic diversity and its relationship with phenotypic characteristics.